Prolyl-tRNA synthetase from Thermus thermophilus is eukaryotic-like but aminoacylates prokaryotic tRNAPro - Yaremchuk, A.D.; Boyarshin, K.S.; Tukalo, M.A. (Вiopolymers and Cell, 2012)
Aim. Cloning, sequencing and expression of the gene encoding prolyl-tRNA synthetase, a class IIa enzyme, from the extreme thermophile T. thermophilus HB8 (ProRSTT). Methods. Search for the ProRSTT gene was performed by Southern blot hybridization with chromosomal DNA, the digoxigenin-labeled PCR fragments of DNA being used as a probe. Results. The gene of T. thermophilus HB8 ProRS has been cloned and sequenced. The predicted 477-amino acid protein is significantly more similar in sequence to eukaryotic and archaeal than to eubacterial ProRS. Sequence analysis shows two distinct structural groups of ProRS which most likely had diverged early in evolution: (1) eukaryotic/archaeal group characterized by the absence of an insertion domain between motifs 2 and 3 and by the presence of an extra C-terminal domain beyond the normal class IIa anticodon binding domain; and (2) prokaryotic with a very large insertion between motif 2 and 3 and no extra C-terminal domain. Conclusions. T. thermophilus proS gene was overexpressed in Escherichia coli and overproduced ProRSTT was purified to high homogeneity. In spite of its eukaryotic-like features, T. thermophilus ProRS exhibited highly specific cross-species aminoacylation. The charging ability of the ProRSTT is restricted to prokaryotic tRNAPro. Keywords: prolyl-tRNA synthetase from Thermus thermophilus, proS gene, сloning, sequencing, expression. Мета. Клонування, секвенування та експресія гена проліл-тРНК синтетази, ферменту IIa класу, з бактерії екстремального термофіла T. thermophilus HB8 (ProRSTT). Методи. Пошук гена Pro RSTT проводили методом Са у зерн-блот-гібридизації з хромосомної ДНК, де як зонди використано мічені дигоксигеніном ПЛРфрагменти ДНК. Результати. Ген ProRSTT HB8 клоновано і секвеновано. Відкрита рамка зчитування гена кодує білок довжиною 477 аміно кислотних залишків, який має більшу гомологію з еукаріотичними і архейними, ніж з бактерійними ProRSs. Дані філогенетичного аналізу засвідчують, що існують дві різні структурні групи ProRS, які розійшлися на початку еволюції: 1) еукаріотично/архейний тип, що характеризується відсутністю вставки в області між мотивами 2 і 3 та наявністю додаткового C-кінцевого домену до звичайного для класу IIa антикодон-зв’язувального домену та 2) про каріотичний тип – з дуже великими вставками між мотивами 2 і 3 та без додаткового C-кінцевого домену. Висновки. З використанням експресуючого вектора ProRSTT суперпродуковано в клітинах Escherichia coli і термостабільний фермент очищено до високого ступеня гомогенності. Незважаючи на приналежність до еукаріотичного типу, ProRSTT показала здатність з високою специфічністю аміноацилювати бактерійну тРНК, у той час як активність відносно тРНК еукаріотів виявилася вкрай низькою. Ключові слова: проліл-тРНК синтетаза з Thermus thermophilus, ген proS, клонування, секвенування, експресія. Цель. Клонирование, секвенирование и экспрессия гена пролил-тРНК синтетазы, фермента IIa класса, из бактерии экстремального термофила T. thermophilus HB8 (ProRSTT). Методы. Поиск гена ProRSTT проведен методом Саузерн-блот гибридизации с хромосомной ДНК, где в качестве зондов использованы меченные дигоксигенином ПЦР-фрагменты ДНК. Результаты. Ген ProRSTT HB8 был клонирован и секвенирован. Открытая рамка считывания гена кодирует белок длиной 477 аминокислотных остатков, который имеет большую гомологию с эукариотическими и архейными, чем бактериальными ProRSs. Данные филогенетического анализа показывают, что существуют две различные структурные группы ProRS, которые разошлись в начале эволюции: 1) эукариотического/архейного типа, характеризующиеся отсутствием вставки в области между мотивами 2 и 3 и наличием дополнительного C-концевого домена к обычному для IIa класса антикодон связывающему домену и 2) прокариотического типа – с очень большими вставками между мотивами 2 и 3 и без дополнительного C-концевого домена. Выводы. С использованием экспресирующего вектора ProRSTT суперпродуцирована в клетках Escherichia coli и термостабильный фермент очищен до высокой степени гомогенности. Несмотря на свою принадлежность к эукариотическому типу, ProRSTT выявила способность аминоацилировать с высокой специфичностью бактериальную тРНК, в то время как активность по отношению к тРНК эукариотов оказалась крайне низкой. Ключевые слова: пролил-тРНК синтетаза из Thermus thermophilus, ген proS, клонирование, секвенирование, экспрессия.